2021
DOI: 10.3390/agronomy11081609
|View full text |Cite
|
Sign up to set email alerts
|

Consortia of Plant-Growth-Promoting Rhizobacteria Isolated from Halophytes Improve Response of Eight Crops to Soil Salinization and Climate Change Conditions

Abstract: Soil salinization is an environmental problem that adversely affects plant growth and crop productivity worldwide. As an alternative to the conventional approach of breeding salt-tolerant plant cultivars, we explored the use of plant-growth-promoting rhizobacteria (PGPR) from halophytic plants to enhance crop growth under saline conditions. Here, we report the effect of five PGPR consortia from halophytes on the growth of eight (alfalfa, flax, maize, millet, rice, strawberry, sunflower, and wheat) of the crops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 50 publications
6
32
0
Order By: Relevance
“…The results showed that all growth parameters were severely decreased in uninoculated plants under stressed conditions. This reduction is in line with the results of many authors working on different plants [2,6,65,66]. It is well known that salt stress induces metabolic perturbation in plants, involving a broad spectrum of metabolic pathways, in both primary and secondary metabolism.…”
Section: Discussionsupporting
confidence: 89%
“…The results showed that all growth parameters were severely decreased in uninoculated plants under stressed conditions. This reduction is in line with the results of many authors working on different plants [2,6,65,66]. It is well known that salt stress induces metabolic perturbation in plants, involving a broad spectrum of metabolic pathways, in both primary and secondary metabolism.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, we tested the effect of PGPR consortia from halophytes on growth, nutrient status, pigment concentrations, secondary metabolites with antioxidant activity, and the response of the photosynthetic apparatus of Swiss chard under salinity conditions. Isolated PGPR from the halophytic rhizosphere were shown to be especially effective in improving the growth of agricultural crops under saline stress conditions [14]. Finally, a single microorganism does not always elicit all the mechanisms to promote plant growth, thus the use of PGPR consortia, instead of a single strain, is of current interest in research [8,15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was not surprising that the biomass production (shoot yield) was only slightly affected by inoculation under the conditions of adequate nutrient supply, as evident in the slight increase in the biomass of the inoculated plants compared to the non-inoculated reference plants. This slight increase, although insignificant, could be due to the plant growth-promoting properties of B. amyloliquefaciens related to the secretion of indole acetic acid (IAA) and 1-aminocyclopropane-1-carboxylic acid deaminase (ACC deaminase) activity, some of which promote increased photosynthetic rates [ 37 , 38 , 39 , 40 ]. Stefan et al [ 41 ] reported increased photosynthetic rates in runner bean upon inoculation with two PGPRs, stating the IAA-producing ability of the bacteria as a possible cause.…”
Section: Discussionmentioning
confidence: 99%